The efficacy of Botulinum Toxin A for spasticity and pain in adults: A systematic review and meta-analysis using the Grades of Recommendation, Assessment, Development and Evaluation approach - Baker, J.; Pereira, Gavin (Sage Publications Ltd, 2013)
Objectives: A systematic review and meta-analysis using the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach to evaluate Botulinum Toxin Type A efficacy on spasticity and pain in the upper/lower limb in adults. Data Sources: Pubmed, Cinahl, Amed, Embase and Cochrane Databases. English language. 1989 to April 2013. Review methods: All randomized controlled trials on adults with spasticity of any origin in the upper or lower limb, treated with a single dose of Botulinum Toxin A, with outcome measures for pain or spasticity. Quality was assessed by GRADE, which uses a transparent, structured process for developing and presenting summaries of evidence, including its quality, for systematic reviews. Results:A total of 37 studies were reviewed. A meta-analysis was carried out on 10 for pain and 21 for spasticity. Evidence quality was low/very low for pain. No significant effect was found in the upper limb (standardised mean difference (SMD) = 0.44, confidence interval (CI) 0.02 to 0.90, Z = 1.88, P=0.06), and no effect was found in the lower limb (risk ratio (RR) = 1.01 CI 0.19 to 5.36, Z = 0.02, P=0.99). Evidence quality for spasticity was moderate. Significant effects were found for Botulinum Toxin in the upper limb (weighted mean difference (WMD) = 0.88, CI 0.63 to 1.14, Z = 6.86, P < 0.00001), and the lower limb (RR=2.42, CI 1.60 to 3.65, Z=4.18, P < 0.0001). Conclusion:The use of Botulinum Toxin A is supported for upper and lower limb spasticity. Further evidence is needed for spasticity-related pain. Evidence quality is reduced by inadequate study design. © 2013 The Author(s).